The Influence of Credit Policy and Lifestyle on the Welfare of Civil Servants - Aswar Anas; M Arif; Darul Ilmi; Supratman Zakir (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research is motivated by the increasing number of civil servants who take bank credit to fulfill their lifestyle which has an impact on decreasing levels of welfare. This research aims to explain the influence of credit and lifestyle policies on the welfare of civil servants, both partially and simultaneously. A quantitative approach with a correlational research type was applied in this research. The research population consisted of civil servants from Madrasah Tsanawiyah Negeri in West Pasaman Regency who took out credit at the bank. The total sample was 70 people, obtained from the results of using total sampling. The instrument used was a questionnaire and processed using correlational data analysis techniques. The research results show that partially the credit policy variable (X1) has a positive and significant effect on welfare, and the lifestyle variable (X2) has a negative and significant effect on welfare. Simultaneously credit policy and lifestyle have a positive and significant effect on welfare.